Different theories & numerical analysis of anchor plates in sand - Niroumand, H. (2011)
This study elucidates the behavior of horizontal anchors in sand based on different theoretical and numerical analyses. This paper presents different theoretical & numerical analysis of anchor plates in loose and dense sand. Numerical methods can be used to estimate the ultimate pullout capacity of anchor plates. This paper discussed different theories and numerical analysis in anchors plates from previous researchers. Analyses, beginning from Meyerhof & Adams (1968) until the most recent analysis such as Sakai & Tanaka (1998) are reviewed. The analysis is pioneered by Vesic (1971), Sarac(1989) and Smit (1989), Krishna(2000), Fargic and Marovic (2003), Merfield and Sloan(2006), Dickin & Lama(2007), Kumar and Bhoi (2008), Kuzer & Kumar(2009) and Niroumand and Kassim(2010). The results are involved different theories and numerical analysis that the results in theoretical and analysis were more than experimental results. According to the results, the ultimate load per bonded length as total length or overburden ratio in the tension anchor plate is increased.